Counter-toppling force on the composite pile with injected grout for a precast spur dike. Issue 11 (7th November 2022) - Zhang, Minxi; Liao, Yikang; Yu, Meixin; Wang, Rui; Yu, Guoliang
Abstract: In this study, a new design of a precast spur dike is described, and a composite pile with injected grout was introduced to enhance the toppling stability of the spur dike. To investigate the toppling process and counter-toppling force of the pile with injected grout, toppling tests of the composite pile with injected grout in sedimentary beds were conducted in the laboratory. The results indicated that the grouting agent reacted with the soil and formed a bulbous wedge, which significantly improved the counter-toppling force of the pile. Four different stages (incipient stage, slow toppling stage, plastic stage, and pull out stage) in the deformation process of the composite pile were observed and described herein. The horizontal counter-toppling force was found mainly influenced by the pile geometry, penetration depth, soil properties, grout volume, and grout injection rate of the grouting agent. Empirical equations for the shape of the wedge and the horizontal forces at the incipient and critical instants of the pile toppling were developed.